Frequent mutations in SH2D1A (XLP) in males presenting with high‐grade mature B‐cell neoplasms. Issue 9 (15th April 2013) - Sandlund, J.T.; Shurtleff, S.A.; Onciu, M.; Horwitz, E.; Leung, W.; Howard, V.; Rencher, R.; Conley, M.E.
Abstract X‐linked lymphoproliferative syndrome (XLP) is caused by mutations in SH2D1A, and is associated with overwhelming infectious mononucleosis, aplastic anemia, hypogammaglobulinemia, and B‐cell lymphomas. However, the frequency of SH2D1A mutations in males who present with B NHL is unknown. Five cases of XLP were diagnosed among 158 males presenting with B NHL (approximately 3.2%). Four of the patients had two episodes of B NHL and one had a single episode of B NHL followed by aggressive infectious mononucleosis. Prospective screening for XLP in males with B‐cell lymphoma at the time of initial diagnosis should be considered. Pediatr Blood Cancer 2013;160:E85–E87. © 2013 Wiley Periodicals, Inc.